Implementation of Lean and Green Manufacturing in The Production of Wifi Sectoral Antennas at CV. XYZ - Ridwan Alief Ramdhan Adi; Endang Pudji W (Green Publisher Indonesia, 2025)
CV. XYZ is a company engaged in manufacturing electronic devices. One of the products produced is the 22 dbi 2.4 ghz MIMO sectoral antenna. This study aims to identify waste in the sectoral antenna production process at CV. Global Access Technology and propose improvements based on lean and green manufacturing principles. To reduce the waste that occurs, the Green Value Stream Mapping (GVSM) method, Waste Assessment Model (WAM), Value Stream Analysis TooL (VALSAT), Root Cause Analysis (RCA), and Failure Mode and Effects Analysis (FMEA) are used. From the data processing and analysis that has been done, the most dominant waste identification results are Motion by 25%, transportation by 17.34%, process by 13.77%, overproduction by 12.97%, defect by 12.60%, inventory by 10.37%, and waiting by 8.15%.For environmental aspects, it produces PCB waste of 13 Kg, aluminum sheet by 7 Kg, PVC by 11 Kg. In the company's production process, the improvement recommendations given are investment in industrial oven machines as a substitute for stoves in the PVC heating process and acrylic bending for the PVC bending process, making maintenance cards for CNC machines that experience downtime, making QC cards for the inspection process using QC cards, scheduling the use of lights in the sectoral antenna production line room, making small versions of sectoral antennas for types with PCB waste that can still be reused, recycling PVC waste to make storage shelves and multilevel transportation aids to move antenna components when going to the assembling process.